Cobalt exchanged zeolites for heterogeneous catalytic oxidation of phenol in the presence of peroxymonosulphate - Shukla, Pradeep; Wang, Shaobin; Singh, Kailash; Ang, Ming; Tade, Moses (elsevier, 2010)
Several cobalt ion-exchanged zeolite catalysts based on ZSM-5, zeolite-A, and zeolite-X were prepared and tested for heterogeneous oxidation of phenol in the presence of various oxidants such as H2O2, persulphate, and peroxymonosulphate. It is found that Co-ZSM-5 is highly effective in heterogeneous activation of peroxymonosulphate to produce sulphate radicals but exhibits low activity for the activation of H2O2 and persulphate for organic oxidation in water. Co-zeolite-A and Co-zeolite-X show much faster reaction rate in homogeneous activation of peroxymonosulphate due to decomposition of the catalysts and leaching of Co ions into aqueous solution. Co-ZSM-5 also presents stable performance in heterogeneous activation of peroxymonosulphate for phenol degradation. The phenol degradation depends on catalyst loading, phenol concentration, oxidant concentration and temperature. Kinetic studies indicate that phenol degradation follows zero-order kinetics with an activated energy of 69.7 kJ/mol.